Pengaruh Harga Tiket Dan Fasilitas Terhadap Minat Berkunjung Di Objek Wisata Pantai Gandoriah Kota Pariaman Menurut Perspektif Ekonomi Syariah - Rinaldi, Afdhol; Juita, Risa; Jonnius, Jonnius; Hermanto, Bambang; Afifah, Dhiya Dwi (MUI Kota Pekanbaru, 2024)
In the tourism sector, ticket prices and facilities are very important for the development of tourist destinations which have a significant impact on the economy and social welfare in Indonesia. Gandoriah Beach in Pariaman, West Sumatra, with affordable entrance fees and adequate facilities, has attracted tourist interest. Even though there was a decrease in visits in 2020 due to the COVID-19 pandemic, efforts to improve facilities by the management continued to attract visitor interest. This research aims to analyze the influence of ticket prices and facilities on visiting interest partially and simultaneously, as well as reviewing it from a sharia economic perspective. This research investigates the impact of ticket prices and facilities on tourist interest in Gandoriah Beach, Indonesia. Despite a drop in visitors during the pandemic, the beach's affordability and improvements made it appealing. Research Goal: Analyze the influence of ticket prices and facilities on tourist interest at Gandoriah Beach. Methodology: Quantitative approach with a survey of 100 visitors (2023) chosen randomly. Findings: Both ticket prices and facilities significantly affect tourist interest. Other factors also play a role. Sharia Economic Perspective: Management should consider Islamic values and social good alongside profit to maximize positive impact.